Pengaruh Permainan Target Terhadap Kemampuan Shooting di Club Sepakbola Remaja Bhayangkara Sungai Rotan Kabupaten Muara Enim - Simanungkali, Janward Gunawan; Yadi, Farhan; Mahendra, Agung (ANTHOR: Education and Learning Journal, 2023)
This study aims to determine how much influence the target game has on the shooting ability of players at the Bhayangkara Youth Football Club Sungai Rotan, Muara Enim Regency. The formulation of the problem in this study is: Is there an effect of target games on the shooting abilities of players at the Bhayangkara Sungai Rotan Youth Football Club, Muara Enim Regency? This research method is a quasi-experimentalresearch with the design or treatment design used as "One group's pre-test-post-test design". The data collection technique in this study used a soccer shooting ability test. The results showed that the initial ability test on the average player's ability to shoot reached an average of 69.50 points, then increased after being given the target game treatment, this was evidenced by the average test results reaching a record of 91.00points. Hypothesis testing states that there is an effect of target game training on shooting ability at the Barayangkara Sungai Rattan Youth Club because Tcount > Ttable (10.30 > 1.729).